PP2A-B55 Holoenzyme Regulation and Cancer - Perrine Goguet-Rubio; Priya Amin; Sushil Awal; Suzanne Vigneron; Sophie Charrasse; Francisca Mechali; Jean Claude Labbé; Thierry Lorca; Anna Castro (Biomolecules, 2020)
Protein phosphorylation is a post-translational modification essential for the control of the activity of most enzymes in the cell. This protein modification results from a fine-tuned balance between kinases and phosphatases. PP2A is one of the major serine/threonine phosphatases that is involved in the control of a myriad of different signaling cascades. This enzyme, often misregulated in cancer, is considered a tumor suppressor. In this review, we will focus on PP2A-B55, a particular holoenzyme of the family of the PP2A phosphatases whose specific role in cancer development and progression has only recently been highlighted. The discovery of the Greatwall (Gwl)/Arpp19-ENSA cascade, a new pathway specifically controlling PP2A-B55 activity, has been shown to be frequently altered in cancer. Herein, we will review the current knowledge about the mechanisms controlling the formation and the regulation of the activity of this phosphatase and its misregulation in cancer.